Respuesta :
[tex]\bold{\huge{\purple{\underline{ Solution }}}}[/tex]
Given :-
- The third term of an AP arithmetic progression is 4x - 2y
- The 9th term of an AP is 10x - 8y
To Find :-
- We have to find the common difference of the given AP?
Let's Begin :-
We know that,
For nth term of an AP
[tex]\bold{\red{ an = a1 + (n - 1)d }}[/tex]
- Here, a1 is the first term of an AP
- n is the number of terms
- d is the common difference
We have ,
[tex]\sf{ a3 = 4x - 2y ...eq(1)}[/tex]
[tex]\sf{ a9 = 10x - 8y ...eq(2)}[/tex]
But, From above formula :-
[tex]\sf{ a3 = a1 + (3 - 1)d}[/tex]
[tex]\sf{ a3 = a1 + 2d...eq(3)}[/tex]
And
[tex]\sf{ a9 = a1 + (9 - 1)d}[/tex]
[tex]\sf{ a9 = a1 + 8d...eq(4)}[/tex]
From eq(1) and eq( 3) :-
[tex]\sf{ a1 + 2d = 4x - 2y }[/tex]
[tex]\sf{ a1 = 4x - 2y - 2d ...eq(5)}[/tex]
From eq(2) and eq( 4) :-
[tex]\sf{ a1 + 8d = 10x - 8y }[/tex]
[tex]\sf{ a1 = 10x - 8y - 8d ...eq(6)}[/tex]
From eq( 5) and eq(6) :-
[tex]\sf{ 4x - 2y - 2d = 10x - 8y - 8d }[/tex]
[tex]\sf{ -2d + 8d = 10x - 4x - 8y + 2y }[/tex]
[tex]\sf{ 6d = 6x - 6y }[/tex]
[tex]\sf{ 6d = 6(x - y) }[/tex]
[tex]\sf{ d = }{\sf{\dfrac{ 6(x - y) }{6}}}[/tex]
[tex]\bold{\blue{ d = x - y }}[/tex]
Hence, The common difference of the given AP is x - y.
The common difference of the given arithmetic progression is; d = x - y
What is the nth term of an arithmetic sequence?
Formula for the nth term of an arithmetic sequence is;
aₙ = a + (n - 1)d
where;
a is first term
n is position of term in the sequence
d is common difference
Thus;
a₃ = 4x - 2y
a₉ = 10x - 8y
Using the general formula, we know that;
a₃ = a + (3 - 1)d
a₃ = a + 2d ----(eq 1)
a₉ = a + 8d -----(eq 2)
Subtract eq 1 from eq 2 to get;
a₉ - a₃ = 6d
Put the given values of a₃ and a₉ to get;
10x - 8y - (4x - 2y) = 6d
6x - 6y = 6d
divide through by 6 to get;
d = x - y
Read more about arithmetic sequence at; https://brainly.com/question/6561461